1998
DOI: 10.1101/gad.12.16.2574
|View full text |Cite
|
Sign up to set email alerts
|

Telomere-mediated chromosome pairing during meiosis in budding yeast

Abstract: Certain haploid strains of Saccharomyces cerevisiae can undergo meiosis, but meiotic prophase progression and subsequent nuclear division are delayed if these haploids carry an extra chromosome (i.e., are disomic). Observations indicate that interactions between homologous chromosomes cause a delay in meiotic prophase, perhaps to allow time for interhomolog interactions to be completed. Analysis of meiotic mutants demonstrates that the relevant aspect of homolog recognition is independent of meiotic recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 52 publications
5
96
0
1
Order By: Relevance
“…Genetic analysis of Saccharomyces cerevisiae strains has indicated that meiotic telomere clustering contributes to efficient homologue alignment and synaptic pairing telomeres. Telomere-associated meiotic protein (Ndj1) is required for tethering meiotic telomeres to the nuclear periphery (7,38). Also, proteins Hop2 and Mnd1 work as a complex to promote meiotic chromosome pairing (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis of Saccharomyces cerevisiae strains has indicated that meiotic telomere clustering contributes to efficient homologue alignment and synaptic pairing telomeres. Telomere-associated meiotic protein (Ndj1) is required for tethering meiotic telomeres to the nuclear periphery (7,38). Also, proteins Hop2 and Mnd1 work as a complex to promote meiotic chromosome pairing (39).…”
Section: Discussionmentioning
confidence: 99%
“…In the fission yeast and Caenorhabditis elegans, loss of telomere function decreases meiotic recombination and increases chromosome missegregation and loss (4)(5)(6). Telomere-mediated chromosome movement and͞or telomere clustering in lower eukaryotes and plants promote homologue pairing (7)(8)(9)(10)(11). Telomeres have been postulated to function similarly in mammalian meiosis (12).…”
mentioning
confidence: 99%
“…Indeed, a role for meiotic telomere reorganization in homology searching through limitation of the available search region has been proposed based on the observation that homologous recombination between heteroalleles placed at ectopic locations is apparently restricted to a lesser extent in an ndj1⌬ mutant than in wild type (Goldman and Lichten 2000). Moreover, a role for Ndj1 in telomere-mediated interactions has been proposed by Rockmill and Roeder (1998).…”
Section: Ndj1 Contributes To Cshj Through the Dsb Repair Pathwaymentioning
confidence: 99%
“…First, the role of NDJ1 in meiotic telomere reorganization could contribute directly to interactions between homologs, independent of interactions mediated through DSB repair, through the role of Ndj1 in tethering telomeres to the nuclear envelope (Rockmill and Roeder 1998). Alternatively, the ndj1⌬ mutation could elicit a defect in CSHJ through a negative effect on recombination.…”
Section: Epistasis Analysis Of Zip3⌬ Zip1⌬ and Mer3⌬ Alleles With Rmentioning
confidence: 99%
“…Ndj1p is a meiosisspecific protein that accumulates at telomeres in S. cerevisiae (15,16) and is required for bouquet formation (17). Deletion of NDJ1 delays axial element formation, homolog pairing, synapsis and onset of the first meiotic division, causes an elevated frequency of nondisjunction and of ectopic recombination, and reduces spore formation and viability (15)(16)(17)(18)(19)(20)(21). Early recombination intermediates form between homologs with wild-type kinetics in ndj1⌬, suggesting that some aspect of bouquet formation is required for the normal coupling of the molecular and cytological events of pairing (22).…”
mentioning
confidence: 99%